29.6k views
0 votes
Solve the equation (linear equation)


((16)/(9)) ^(2x +5) =((3)/(4))^(x-7)

User Cvacca
by
5.2k points

1 Answer

3 votes

Answer:
x=-(3)/(5)

Explanation:

By the negative exponent rule, you have that:


((1)/(a))^n=a^(-n)

By the exponents properties, you know that:


(m^n)^l=m^((nl))

You can rewrite 16 and 9 as following:

16=4²

9=3²

Therefore, you can rewrite the left side of the equation has following:


((4^2)/(3^2))^((2x+5))=((3)/(4))^((x-7))\\\\((3^2)/(4^2))^(-(2x+5))=((3)/(4))^((x-7))\\\\((3)/(4))^(-2(2x+5))=((3)/(4))^((x-7))

As the base are equal, then:


-2(2x+5)=x-7

Solve for x:


-2(2x+5)=x-7\\-4x-10=x-7\\-4x-x=-7+10\\-5x=3\\x=-(3)/(5)

User Hbceylan
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.